2022
DOI: 10.3390/pharmaceutics14101993
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Docetaxel-Containing Emulsion for Drug Release Kinetics and Lipid Peroxidation

Abstract: Docetaxel (DTX)-based formulation development is still confronted with significant challenges, due to its refractory solubility and side effects on normal tissues. Inspired by the application of the transdermal drug delivery model to topical treatment, we developed a biocompatible and slow-release DTX-containing emulsion via self-assembly prepared by a high-speed electric stirring method and optimized the formulation. The results of accelerated the emulsion stability experiment showed that the emulsion prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…Our results confirmed that the DTX release was slower from the chitosomes than from the non-coated liposomes ( Figure 5 c,d). Both liposome groups showed a first-order DTX release profile consistent with previous reports [ 69 ]. As opposed to non-coated anionic liposomes, the DTX release from chitosomes was expected to be prolonged due to the coating, which provides an external physical barrier enveloping the liposomes [ 47 , 70 ].…”
Section: Resultssupporting
confidence: 90%
“…Our results confirmed that the DTX release was slower from the chitosomes than from the non-coated liposomes ( Figure 5 c,d). Both liposome groups showed a first-order DTX release profile consistent with previous reports [ 69 ]. As opposed to non-coated anionic liposomes, the DTX release from chitosomes was expected to be prolonged due to the coating, which provides an external physical barrier enveloping the liposomes [ 47 , 70 ].…”
Section: Resultssupporting
confidence: 90%
“…The improved Franz diffusion well was adopted [ 70 ], with a diffusion area of 1.825 cm 2 and the receiving cell volume was 15 mL. We prepared three sets of controllable temperature magnetic stirrers (85-2, Changzhou Yineng Experimental Instrument Factory, Changzhou, China), and set the temperatures to 32 °C, 35 °C, and 37 °C, respectively, which were stable between ±0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…At different time points or different voltages, the movement distance of BBH was measured to analyze the movement of drugs in Gel–Alg hydrogels at different ratios (2:1, 3:1 and 4:1) of gelatin and sodium alginate. Skin tissue was obtained according to the method previously reported in our laboratory [ 33 ], and then it was added between agarose gel and Gel–Alg hydrogel, and BBH solution or BBH–Gel–Alg was added into the whole of agarose gel, and the drug migration distance was recorded at 0, 1, 2, 4 and 6 h. After 6 h, the Gel–Alg hydrogel was stirred in sections, centrifuged at 6000 rpm/min for 10 min, and the supernatant was taken to measure the absorbance value and calculate the BBH content.…”
Section: Methodsmentioning
confidence: 99%